The Potential of Tube Industry Development in Conditions of Instability - A. P. Garnov; O. V. Devyatkin; G. A. Rybina (Вестник Российского экономического университета имени Г. В. Плеханова)
The research deals with estimating the potential of Russian enterprises of tube industry and possibilities of their efficient adaptation to fast changes. Academic results of the research include systematization, summarizing and author’s appraisal of processes taking place in Russian tube industry, as well as proposals aimed at its development. According to the research, Russian tube industry rather quickly adapts to changes and is still stable in spite of difficult situation and high sectoral risks. Today the potential of the increase in home demand for tubes is not realized in full, especially for products with high added value. Tube industry is facing the problem of importsubstitution in equipment purchase and production modernization. To resolve it a set of measures is necessary, such as starting the mechanism of innovation development in machine-building manufacturing; working-out the program of developing home industry of electronics, software, systems of management and engineering; motivating the growth in production capacities of machine-building enterprises. It is necessary to raise investment from countries importing tube products in Asia, Africa and Middle East. These regions can become both the marketing targets and sources of investment. In conditions of instability tube industry is strategically important for the country and needs measures of state support.